Comprehensive evaluation of the impact of workplace exposures on physician-certified sick leave in the general working population - Tom Sterud; Andrea R Marti; Eirik Degerud (BMC, 2024)
Abstract Background Our objective was to quantify the prospective associations between work factors across chemical, physical, mechanical, and psychosocial domains and the onset of medically certified sick leave. Methods Eligible respondents were interviewed in 2009, 2013, or 2016 and were registered in the national sick leave register with an employee relationship lasting more than 50 working days during the year of the survey interviews and the following year (n = 15,294 observations). To focus on the onset of high-level sick leave (HLSL; >16 days a year), we excluded individuals with HLSL during the survey year (baseline). We then used mixed-effect logistic regression models to assess prospective associations between self-reported work conditions and the occurrence of doctor-certified HLSL in the following year. Results The average occurrence of HLSL was 13.1%. After adjusting for sex, age, level of education, chronic health problems, and smoking, we observed an exposure-response relationship between cumulative exposure to work factors within all domains and the occurrence of HLSL. When evaluating the impact of combined exposures, predicted odds ratios (OR) for employees exposed to 1, 2, and 3 or more work factors within all domains were 1.60 (95%CI 1.32 − 1.94), 2.56 (95%CI 1.73 − 3.74) and 4.09 (95%CI 2.28 − 7.25), compared to those not exposed. Conclusions The results support the notion that exposure to multiple work factors in various domains, including psychosocial, mechanical, chemical, and physical work conditions, is associated with an increased risk of high-level sick leave. Employers and occupational health professionals should consider the joint impact of these domains when designing interventions.